Determinasi Pemanfaatan Informasi Akuntansi pada Usaha Mikro Kecil Menengah - Erike Fitriana; Arik Susbiyani; Diyah Probowulan (BUDGETING : Journal of Business, Management and Accounting, 2021)
This study aimed to determine the effect of business scale, length of business, and the last education of business owners on the use of accounting information. This research method is descriptive quantitative. In collecting data, this study used a questionnaire distributed to the owners or leaders of SMEs. The regression model used in this study is a multiple linear regression model with the help of SPSS (Social Sciences Statistical Package). The results showed that the multiple regression equation was Y = 31,821 + 2,751X1 + 3,802X2 + 4,304X3. In conclusion, the factor of business scale, length of business and the last education of the owner had a positive and significant effect on the use of accounting information in SMEs. Keywords: Length of Business, Owner's Last Education, Use of Accounting Information, Business Scale, UMKM